PENGARUH KOMUNIKASI, TINGKAT PENDIDIKAN, DAN PROFESIONALISME TERHADAP KUALITAS PELAYANAN DI KANTOR BERSAMA SAMSAT KABUPATEN PAMEKASAN - jurnalmap map; Septia Wahyudi; Indra Prasetyo; Chamariyah ÔÇÄ (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
The objective of this research is to obtain the right data and information to analyze the data. Specifically this study aims: To determine the effect of communication, level of education and professionalism on the quality of service in the office with Samsat Pamekasan District. The author makes an employee at the Office Samsat Pamekasan as a population, which totals amounted to 34 people. Given the population is quite small so that the sample taken as large as the population (total sample of 34 people). Based on the results of this research data analysis, communication, education level and professionalism simultaneously and significantly influence the quality of service in the office together Samsat Pamekasan District. While the partial test is only the variable level of education and professionalism that positively affect the quality of service in the office with Samsat Pamekasan District.Keywords: communication, level of education, professionalism, service quality